Electrospun conductive polyaniline–polylactic acid composite nanofibers as counter electrodes for rigid and flexible dye-sensitized solar cells - Mhaisalkar, Subodh Gautam (2013)
Conductive polyaniline doped with 10-camphorsulfonic acid (PANI·CSA) blended with polylactic acid (PLA) composite films are directly deposited on rigid fluorine-doped tin oxide and flexible indium tin oxide-coated polyethylene naphthalate substrates by using a simple electrospinning method. The scanning electron microscope and atomic force microscope images show that the PANI·CSA–PLA film is assembled from about 200 nm-diameter nanofibers, with a generally uniform thickness of about 2 μm. The three-dimensional porous fibrous PANI·CSA–PLA films indicate good electrocatalytic performance for I3−/I− electrolyte, demonstrated by electrochemical impedance spectra and cyclic voltammetry measurements. The photoelectric conversion efficiency of the dye-sensitized solar cells (DSCs) firstly based on such rigid and flexible PANI·CSA–PLA counter electrodes achieves 5.3% and 3.1% under 1 sun illumination of 100 mW cm−2 (AM 1.5), respectively, which is close to that of sputtered Pt-based DSCs. In addition, the rigid PANI·CSA–PLA-based DSC demonstrates good stability. As the PANI·CSA–PLA counter electrodes can be obtained in a short time at room temperature, they are potentially applicable in large-area DSCs and suitable for flexible DSCs.